READING QUESTIONS QUALITY IN AN ENGLISH WORKSHEET FOR GRADE XI OF VOCATIONAL HIGH SCHOOL BASED ON REVISED BLOOM’S TAXONOMY - Ummi Kalsum Purba; Nora Ronita Dewi (Universitas Negeri Medan, 2020)
This research is aimed to analyze the reading questions quality in an English worksheet for grade XI of Vocational High School based on Revised Bloom’s taxonomy. This study is conducted by descriptive method, with qualitative as well as quantitative area. The subject of this study is reading questions which are taken from English worksheet for grade XI published by Surya Grafika Mandiri. Since this study uses observation method, the instruments of collecting data is by using checklist. The result of the checklist was analyzed both as qualitative and quantitative data. These data are the reading questions in English worksheet based on Revised Bloom’s Taxonomy. The final result was the quality of reading questions categorized into each types of cognitive domain of Revised Bloom’s Taxonomy.